Multilevel Seismic Damage Behavior Correlation Analysis for RC Framed Structures - Jianguang Yue (Advances in Materials Science and Engineering)
Five structural levels, that is, material level, section level, member level, storey level, and structure level, were proposed to analyze the multilevel nonlinear mechanism of the reinforced concrete (RC) framed structures. Based on the presented deformation equivalent principle, a generalized stiffness damage model was developed for each structural level. At each structural level, the stiffness damage value can be calculated by the integration of the material stiffness damage. Furthermore, an impact factor was proposed to reflect the damage correlations between different structural levels. In order to verify this method, the proposed method was used to study the damage evolutions at various structural levels of a 12-storey frame structure. The numerical model utilizing the proposed analysis method produces results in good agreement with the test results of the 12-storey frame structure. It shows that the proposed method is useful to assess the structure multilevel damage performance and to design a new structure.